La enseñanza de la geografía de riesgos y sistemas de información geográfica durante la crisis sanitaria covid-19 en las carreras de Ciencias Sociales y Pedagogía de la Historia en la UNACH - Curimilma Palacios, Cecibel del Cisne (2022)
The present research work entitled "THE TEACHING OF RISK GEOGRAPHY AND GEOGRAPHIC INFORMATION SYSTEMS DURING THE COVID-19 HEALTH CRISIS IN THE CAREERS OF SOCIAL SCIENCES AND HISTORY PEDAGOGY AT UNACH" analyzed the degree of methodological effectiveness within the teaching and learning process of the subjects Risk Geography and Geographic Information Systems in the virtual modality during the pandemic crisis caused by COVID-19. The methodology used was quantitative since the information was collected through surveys applied to the eighth and fourth semesters of the current course, Pedagogy of History and Social Sciences of the National University of Chimborazo. Due to its descriptive type, notable characteristics were identified based on comparing the methodologies used before and during the pandemic, being a comparative study for which bibliographic information was valuable to support the theoretical foundation. The students of both careers, through the surveys, suggest the development of new methodological proposals for the strengthening of Geography in the Social Sciences. The study population consisted of 45 students. The technique applied was the survey using a questionnaire as an instrument, which allowed asserting the methodology's effectiveness used in the mentioned subjects has been excellent, corresponding to the values obtained. After the results' analysis and interpretation, the applied methodology's effectiveness was the conclusion. Therefore, an educational web page was made as a proposal, which helps to have a significant learning in the different subjects. Education will be face-to-face mode. And for this purpose, the work tools will be used again. Considering that these tools will help to reach a better study level, and for this reason, the use of several methodologies will be indispensable with the purpose that the student can socialize them. Keywords: Methodologies, learning-teaching, COVID-19.